A Canvas by the Madrid Painter Diego González de la Vega in the Parish Church of Nombela (Toledo) (BSAA arte, 2019)
Information about a canvas depicting St John the Baptist, signed and dated by the Madrid painter Diego González de la Vega in 1683 and preserved at the top of a side altarpiece of the parish church of Our Lady of the Assumption of Nombela (Toledo, Spain).
Keywords: Diego González de la Vega; St John the Baptist; Baroque painting; Madrid school; Nombela (Toledo)